Improving the Seventh-Grade Students’ Speaking Ability Through Fishbowl Game at SMP Muhammadiyah I Genteng Academic Year - Yayah Ikhda Nevia; Noor Faridha (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2024)
most important thing in therriculum. The result of learning English for junior high school is communication between oral and written. The limitation is the ability to understand sentences in English. Refers to the KTSP curriculum or the education unit-level curriculum. The emphasis in this curriculum is on speaking and writing skills. Ability here can be interpreted as a limitation of literacy function, namely that students are able to interpret and make texts in the form of procedure text, recount text, narrative text, and descriptive text. Procedure text is used to tell about making, or doing something. Often the students find it difficult to do that. The students find it difficult to learn and cannot express again, the teacher must find an easy and effective way, The problem in this research is "how to apply the Fishbowl game to improve speaking habits at SMP MUHAMMADIYAH I GENTENG in the 2019/2020 academic year. This Classroom Action Research has several stages: planning, implementing, observing, and reflecting. The result is that the minimum standard in cycle 1 is 57% and cycle 2 is 89%. It can be concluded that this method has reached the target of 75%. It can be concluded that the learning process has been fulfilled by using the fish bowl game method to improve speaking skills at SMP MUHAMMADIYAH I GENTENG for the 2019/2020 school year.